Den norske antarktisekspedisjonen 1996/97: forskningsaktiviteter - Winther, Jan-Gunnar (Polarboken, 1998)
Keywords: Dronning Maud Land; forsking; klima

Studies and monitoring of climate-sensitive melt areas in Jutulgryta - Winther, Jan-Gunnar; Liston, Glen E; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; hydrologi; klima; meteorologi

A century of accumulation and temperature changes in Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Gundestrup, Niels; Mayewski, Paul; Whitlow, Sallie; Twickler, Mark (Journal of Geophysical Research: Atmospheres, 1996)
Keywords: Dronning Maud Land; akkumulasjon; klima; målinger; snø; temperatur

High resolution climatic information from short firn cores, western Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn (Climatic Change, 1994)
In this paper a detailed record of major ions from a 20 m deep firn core from Amundsenisen, western Dronning Maud Land, Antarctica, is presented. The core was drilled at 75° S, 2° E (2900 m a.s.l.) during austral summer 1991/92. The following ions were measured at 3 cm resolution: Na+, Mg2+, Ca2+, Cl−, NO3−, S04 2− and CH3SO3H (MSA). The core was dated back to 1865 using a combination of chemical records and volcanic reference horizons. The volcanic eruptions identified in this core are Mount Ngauruhoe, New Zealand (1974–75), Mount Agung, Indonesia (1963), Azul, Argentina (1932), and a broad peak that corresponds in time toTarawera, New Zealand (1886), Falcon Island, South Shetlands, Southern Ocean (1885), and Krakatau, Indonesia (1883). There are no trends in any of the ion records, but the annual to decadal changes are large. The mean concentrations of the measured ions are in agreement with those from other high-altitude cores from the Antarctic plateau. At this core site there may be a correspondence between peaks in the MSA record and major El Niño–Southern Oscillation events.
Keywords: Dronning Maud Land; glasiologi; kjemi; klima

The climate of Halley, Antarctica - Hanssen-Bauer, Inger; DNMI (Det norske meteorologiske institutt, 1992)
Keywords: Antarktis; klima; meteorologi

Perspektiver for norsk forskning i Antarktis : langtidsplan for norsk Antarktis-forskning, høringsutkast av kapittel 6: framtidig norsk forskning - Omholt, Anders; Nygard, Jarle (Nasjonal komite for miljøvernforskning, NAVF, 1991)
Keywords: Antarktis; Norge; glasiologi; klima; marinøkologi; miljøforskning; polarforskning; polarområdene

lnvestigating climate change by digital analysis of satellite imagery of blue ice extent in Antarctica - Orheim, Olav; Luchitta, Baerbel (Annals of Glaciology, 1990)
Landsat-5 Thematic Mapper (TM) and SPOT data collected two years apart from an identical area of Dronning (Queen) Maud Land, Antarctica, have been analyzed to detect variations in surface features that may signal climatic change, and to establish a technique that readily identifies such changes. We found that selective principal component analysis (Chavez and Kwarteng 1989), on band ratios of near-IR/green, highlights changes in blue ice areas. The formation and preservation of blue ice is poorly understood, but we suggest that it generally takes longer to increase a blue ice area than to decrease it, and that blue ice extent is most sensitive to changes in accumulation rate. The investigated blue ice area shows a decrease in extent over the two-year period caused by incursion of snow that probably resulted from an increase in accumulation rate. Comparison of two TM images collected 18 days apart shows that transitory snow drifts have little effect on blue ice extent.
Keywords: Dronning Maud Land; glasiologi; klima

Zonality of climate and plant distributions in some Arctic and Antarctic regions - Engelskjøn, Torstein (Norsk Polarinstitutt, 1986)
Keywords: Bouvetøya; Dronning Maud Land; botanikk; klima; planter; polarområdene

Lave temperaturer i Antarktis - Orheim, Olav (Polarboken, 1966)
Keywords: Antarktis; klima; meteorologi

Cooling effect of an Antarctic climate on man : with some observations on the occurence of frostbite - Wilson, Ove (Norsk Polarinstitutt, 1963)
Keywords: Dronning Maud Land; forfrysning; klima; medisin

Verdien av de meteorologiske observasjoner fra hvalkokeriene = The value of meteorological observations from whaling factory ships - Vowinckel, E (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; klima; meteorologi; observasjoner

Polaraaret 1932-1933 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; forskning; klima; meteorologi; oseanografi